Relationships among childhood experiences, happiness and social media addictions in adolescents - Yasin Demir (Educational Process: International Journal)
Background/purpose – The use of social media has become commonplace among adolescents. However, excessive use of social media causes addiction in some cases. In this context, it is considered important to investigate the factors related to social media addiction. The aim of this study is to investigate the relationships among childhood experiences, happiness, and social media addiction in adolescents.